The genus Nigritella (Orchidaceae) in the Iberian Peninsula - Llorenç Sáez (Anales del Jardín Botánico de Madrid)
As a result of the revision of Nigritella L.C.M. Richard in the Iberian Peninsula, here we recompile information of its variability, taxonomy, nomenclature and chorology. Two taxa are recognized: Nigritella austriaca subsp. iberica (Teppner & E. Klein) L. Sáez, comb. nov. and N. gabasiana Teppner & Klein, and the presence of N. corneliana is excluded. Detailed phytodermologic analysis showed that size of guard cells is useful for species identification.